Wild edible plants in four Agni tribes of Central-east and Northeast of Côte d’Ivoire: a comparative study - Djah François Malan; AMANI LÉOPOLD LITTA; MÉNÉKÉ DISTEL KOUGBO; AMADOU LAMINE DIOP; KOUASSI GÉRARD KOUASSI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Malan DF, Litta AL, Kougbo MD, Diop AL, Kouassi KG. 2020. Wild edible plants in four Agni tribes of Central-east and Northeast of Côte d’Ivoire: a comparative study. Biodiversitas 21: 4896-4902. An ethnobotany survey was carried out in twelve villages of the four Agni tribes from the Center-east to Northeast of the Côte d'Ivoire, in order to assess the evolution of the knowledge and know-how of these peoples concerning wild edible plants. Frequency of citations and the Smith index of each of edible plants were obtained with data from the survey of 571 informants (279 men and 292 women). Factorial analysis of the correspondences was also performed in order to reveal the similarities between the different tribes. In total, 77 plant species (36 families and 67 genera) were cited as consumed by humans. The most used parts are the fruits (65.38%), and leaves (24.36%). Analysis of the similarities shows that only 18.82% of these species are common to the four tribes. In addition, knowledge related to wild edible plants is gradually degrading, for several reasons, including obsolescence of use and the unavailability of plants due to environmental degradation. Thus, the valuation and protection of these resources would be beneficial to populations.